2018
DOI: 10.4274/jcp.2018.0047
|View full text |Cite
|
Sign up to set email alerts
|

Picky Eating and Risk Factors in Children

Abstract: Seçici yeme, çocukluk döneminde yaygın olarak görülen beslenme sorunlarından biridir. Çeşitli yeme davranışlarının bileşiminden oluşmakta olup, hem alışılmış, hem de yeni besinlerin reddedilmesi, güçlü besin tercihleri ile yetersiz miktarda veya çeşitlilikte besin tüketimi ile karakterizedir. Geçici veya hafif seçici yeme davranışları normal gelişimin bir parçası olarak görülebilmektedir. Fakat erken çocukluk döneminde görülen seçici yeme, bazı durumlarda kaçıngan / kısıtlayıcı yeme bozukluğu için öncül olabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 33 publications
0
5
0
6
Order By: Relevance
“…Although there is no study examining the prevalence of PE in Turkish children in the literature, according to a study conducted for the problematic eating behaviors in children 12–74 months, in Turkey, 39% of mothers stated that their children were picky eater [ 16 ]. Due to the differences in the definition of PE and methodological differences of the studies, the frequency and prevalence of PE has been reported to be in a wide range in different studies [ 25 ]. In their review, Samuel et al divided the studies into 3 groups according to the way children questioned and reported the prevalance ranges of PE between (i) 12.3%-49% in 3 studies using 'one closed-ended question’; (ii) 6.6%-59.3% in 14 studies using ‘a single question selected from predetermined possible answers’ (iii) 5.5%-70.1% in 21 studies using ‘several question and answer combinations’ [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no study examining the prevalence of PE in Turkish children in the literature, according to a study conducted for the problematic eating behaviors in children 12–74 months, in Turkey, 39% of mothers stated that their children were picky eater [ 16 ]. Due to the differences in the definition of PE and methodological differences of the studies, the frequency and prevalence of PE has been reported to be in a wide range in different studies [ 25 ]. In their review, Samuel et al divided the studies into 3 groups according to the way children questioned and reported the prevalance ranges of PE between (i) 12.3%-49% in 3 studies using 'one closed-ended question’; (ii) 6.6%-59.3% in 14 studies using ‘a single question selected from predetermined possible answers’ (iii) 5.5%-70.1% in 21 studies using ‘several question and answer combinations’ [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seda Şengüzel 1 , Elvan Yılmaz Akyüz 2 Geliş tarihi/Received: 02.12.2021 • Kabul tarihi/Accepted: 20.04.2022…”
Section: Validity and Reliability Study Of The Turkish Version Of The...unclassified
“…Yeme davranışı, yaşamın ilk yıllarında gelişen ve yetişkinlik döneminde de şekillenmeye devam eden bir süreci kapsamaktadır (1,2). Bu nedenle çocukluk dönemi, sağlıklı beslenme alışkanlıklarının kazandırılmasında büyük bir öneme sahiptir.…”
Section: Introductionunclassified
See 2 more Smart Citations